The Role of Fuel Bed Geometry and Wind on the Burning Rate of Porous Fuels - McAllister, Sara (Frontiers in Mechanical Engineering, 2019)
The vast majority of wildland fires occur in windy conditions. However, most operational wildland fire models do not account for changes in burning rate or duration due to wind as no simple model exists. To gain some understanding of how wind and fuel bed properties interact to influence the burning rate and duration of wildland fuels, a relatively simple fuel bed, wood cribs, was first considered. The burning rate of twenty three crib designs was measured in a wind tunnel under a range of windspeeds from 0 to 0.7 m/s. Fuel element thickness varied from 0.32 cm to 1.27 cm and fuel bed width from 12.7 cm to 60.96 cm. A range of crib porosities was tested as well covering the loosely-packed to densely-packed regime. A clear threshold behavior of the burning rate was seen depending on fuel bed geometry. For fuel beds with element length to thickness ratio (l/b) less than 30, the burning rate increased with wind. However, for fuel beds with element length to thickness ratio larger than 30, the burning rate actually decreased with wind. This change in burning rate was linked to a visual change in burning behavior. When the burning rate increased, the wind and flames were observed to penetrate the internal portions of the fuel bed and the crib would burn uniformly. When the burning rate decreased, the wind and flames did not penetrate the entire fuel bed and the burning front would most often propagate from the upwind edge to the downwind edge. It appeared that for these fuel bed geometries the wind was forced around the fuel, preventing any horizontal or, more importantly, vertical flow through the bed. These results are likely most applicable to isolated, small clumps of elevated fuel where the wind has the opportunity to divert around the fuel bed. Future work will include experiments that force the airflow through the fuel bed.